English monophthongs produced by Bangla speakers / Sumsun Naher - Sumsun , Naher (2018)
English was formally introduced in Bangladesh during the period of British colonization in the 16th to 19th century. The use of English in Bangladesh has developed linguistically since the British left in 1947. There are obvious differences in the English pronunciation of Bangla speakers but there is a dearth of research in the area. In an attempt to fill this gap, this study investigates the production of English vowels by the Bangla speakers through an acoustic study. Data were collected from 10 Bangla English speakers, five males and five females who speak Bangla as their first language. The questions addressed in this study are: (1) What are the qualities of English vowels produced by Bangla speakers based on acoustic analysis of the first (F1) and second formant (F2)?; (2) What is the extent to which Bangla speakers contrast typical English vowel pairs in terms of vowel length and vowel quality? The data were recorded in a word list context. A total of 550 tokens were annotated and measured and using Praat. The findings indicated a similar pattern to many other varieties of English where vowel quality was concerned, where the speakers did not display vowel quality contrast for typical vowel pairs. However, they appeared to maintained length contrast for most of the vowel pairs except the /u:/-/ʊ/ for both male and female speakers, and /e/-/æ/ for female speakers.